Validation of a counseling guide for adherence to antiretroviral therapy using implementation science - Flor Yesenia Musayón-Oblitas; Cesar Paul Cárcamo; Sarah Gimbel; Juan Ignacio Echevarria Zarate; Ana Beatriz Graña Espinoza (Universidade de São Paulo, 2020)
Objective: to determine the contents that must be included in the usual counseling to improve the adherence to antiretroviral therapy (ART) of HIV patients, according to their different levels of alcohol consumption, and to determine the validity of the Counseling Guide in improving the adherence to ART in patients who consume alcohol using Implementation Science. Method: this is an observational study with formative and validation phases. The formative phase defined the content, approach and structure of the counseling. Validation included focus groups with patients and nurses, trial process by an expert and a pilot test. The criteria evaluated based on Implementation Science were: intervention source, evidence strength and quality, relative advantage, and complexity. The following criteria were also evaluated: usefulness, practicality, acceptability, sustainability, effectiveness; content consistency and congruence; procedural compliance and difficulties, and time spent in counseling. Results: the strength of evidence of the counseling is High-IIA, with strong level of recommendation and presenting usefulness, practicality, acceptability, sustainability and effectiveness. Eight in 11 experts argued that the Guide is clear, consistent and congruent. Initial counseling takes around 24 minutes; and follow-up counseling, 21. The instruments of the Guide present reliability levels between good and high (0.65 ≥ alpha ≤ 0.92). Conclusion: the Counseling Guide is valid to improve the adherence to antiretroviral therapy in patients who consume alcohol.